Inhibitory effect of some selected compounds on Polyphenol oxidase activity of Oyster mushroom (Pleurotus sajor-caju) - Khare, Vinay Kumar (Mushroom Research, 2017)
Present study was performed to evaluate the inhibitory effect of some selected compounds on Polyphenol oxidase activity of oyster mushroom (Pleurotus sajor-caju). Ascorbic acid, citric acid, sodium chloride, calcium chloride and EDTA were used at three different concentration levels viz., 1%, 0.5%, and 0.25% and studied to evaluate the sensitivity of Polyphenol oxidase towards them. All used compounds were found potentially inhibitor for enzyme, singularly ascorbic acid shows highest activity at all used concentrations followed by citric acid and sodium chloride. However EDTA and calcium chloride were found effective only at higher concentration.